1972
DOI: 10.1063/1.1677651
|View full text |Cite
|
Sign up to set email alerts
|

Slow Electronic Relaxation in T52−A11 Spin Equilibria of Tris(2-methyl-1,10-phenanthroline)Iron(II) Complexes: A Mössbauer Effect Study

Abstract: Articles you may be interested inThe effect of pressure on the thermal hysteresis of the firstorder spin transition in bis(1,10 phenanthroline2carbaldehyde phenylhydrazone) iron (II) complexes J. Chem. Phys. 83, 3055 (1985); 10.1063/1.449209 Electron Transfer Rates for Unsubstituted and Dimethylsubstituted Tris(1,10phenanthroline) Iron(II) and (III) Ions from NMR Studies Erratum: Nuclear Magnetic Resonance Studies of Electron Transfer between Tris(2,2′ dipyridyl)osmium(II) and (III) Ions, between Bis(cyclopent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(4 citation statements)
references
References 17 publications
(4 reference statements)
1
3
0
Order By: Relevance
“…The observations are similar to those made in a study on the polycrystalline compound [Fe(2-CH3phen) 3] (C104)2,2 except that in the present case the spin conversion from high spin (S = 2) to low spin (S = 0) is shifted to higher temperatures, whereas in the 2-CH3phen complex no spin singlet state is observable at room temperature. 3 Similarly to the findings in the 2-CH3phen complex we again observe two high-spin iron(II) resonance doublets besides the lAlg(Oh) ground state in the Mdssbauer spectra. Their electronic nature may be derived from the temperature dependence of the quadrupole splitting by a calculational method originally proposed by Ingalls,13 employing the general expression £9( ) = l-e2Q( 1 -R)<.r~3)°3ia2 [F(5t, 2 0, T)]…”
Section: Resultssupporting
confidence: 83%
“…The observations are similar to those made in a study on the polycrystalline compound [Fe(2-CH3phen) 3] (C104)2,2 except that in the present case the spin conversion from high spin (S = 2) to low spin (S = 0) is shifted to higher temperatures, whereas in the 2-CH3phen complex no spin singlet state is observable at room temperature. 3 Similarly to the findings in the 2-CH3phen complex we again observe two high-spin iron(II) resonance doublets besides the lAlg(Oh) ground state in the Mdssbauer spectra. Their electronic nature may be derived from the temperature dependence of the quadrupole splitting by a calculational method originally proposed by Ingalls,13 employing the general expression £9( ) = l-e2Q( 1 -R)<.r~3)°3ia2 [F(5t, 2 0, T)]…”
Section: Resultssupporting
confidence: 83%
“…These studies show that for the Fe 2+ d 6 configuration in an octahedral field, there is a value for the ligand field strength beyond which the ground state of the Fe 2+ ion changes from a quintet to singlet state. Hence, a spin crossover or spin transition can be expected to be induced when the ligand field strength about the Fe 2+ ion is in the vicinity of this critical value such that minor external perturbations can tip the scales in favor of one or the other for the ground states. , For example, studies of Fe 2+ complexes using Mossbauer spectroscopy indicate that quintet–singlet transitions of ground-state Fe 2+ are temperature dependent. Other studies have shown that the ligand structure can influence the symmetry of the Fe 2+ ion environment causing spin transition. Extensive data exist establishing that nearly all six-coordinate Fe 2+ complexes of the type Fe 2+ (Phen) 3 have diamagnetic ground states . In the current studies, the progressive addition of Phen ligands to the Fe 2+ center effects spin pairing in the Fe 2+ ion only on coordination of the third Phen ligand according to B3LYP results.…”
Section: Discussionmentioning
confidence: 99%
“…A related observation, as far as Mossbauer spectra are concerned, has been made in the compound [Fe(2-CH3phen)3](C104)2 where a considerable broadening of the Mossbauer lines was encountered for the 5T2 phase. 26 This compound is involved in a very gradual high-spin (5T2)low-spin ('A,) transition. Subsequently, the lines were resolved by Fleisch et al27 into two separate 5T2 doublets over the entire temperature range between 4.2 and 295 K. The two doublets have been attributed to two different lattice sites of high-spin iron(II) characterized by a reversal of the orbital ground state, viz.,5A, and 5E, of D3 symmetry.…”
Section: Discussionmentioning
confidence: 99%